Adenosine triphosphate (ATP) bioluminescence-based strategies for monitoring atmospheric bioaerosols. (2nd December 2022) - Zhang, Yueqi; Liu, Bing; Tong, Zhaoyang
ABSTRACT: Bioaerosols play a momentous role in the transmission of human infectious diseases, so there has been increasing concern over their exposure in recent years. Bioaerosol monitor is crucial in environmental fields. Based on the universal existence of Adenosine triphosphate (ATP) in bioaerosols, ATP bioluminescence can be used as a powerful technique to detect bioaerosols without interference from non-bioaerosols. When ATP is released from bioaerosols, they can quantify microbial biomass by ATP bioluminescence. In this review, we provide the latest methodological improvements that enable more reliable quantification of bioaerosols in complex environmental samples, especially the use of ATP bioluminescence in this era of technological advancement via the following routes: lower sample content for the trace existence of bioaerosols in the atmosphere, higher sensitivity of ATP bioluminescence reaction system and shorter process times. We also highlight the new techniques in improving the efficiencies of these monitoring processes. The purpose of this paper is to make more people realize the great potential of the ATP bioluminescence system for monitoring airborne microorganisms. Additionally, the present work intends to increase people's awareness of developing novel technology combined with ATP bioluminescence reaction system to realize rapid, real-time, and sensitive sensing of bioaerosols. Implications : The ATP bioluminescence methodology can not only eliminate the interference of co-existing nonbiological (fluorescent or PM) but also significantly improve the efficiency of bioaerosol. Recent progresses, such as the application of ATP fluorescence technology in bioaerosol monitoring, indicating that the efficiency and sensitivity are possible to be further improved. Nevertheless, there is no reviews address these advances and deeply analyze the application of ATP fluorescence technology in this field. his contribution will attract wide attention from both academic and industrial communities of this field, as well as researchers engaging in environmental monitoring. Furthermore, the strategies and techniques of studying the ATP bioluminescence reviewed here is instructive for environment monitoring in various fields. Therefore, in view of significance and broad interest, we feel strongly that our critical review is very essential to the field of public health security, pharmaceutics, anti-bioterrorism, etc., and would like it to be published in Journal of the Air & Waste Management Association.